Evaluating N-acetylcysteine for early and end-of-treatment abstinence in adult cigarette smokers. (1st August 2021) - McClure, Erin A.; Wahlquist, Amy E.; Tomko, Rachel L.; Baker, Nathaniel L.; Carpenter, Matthew J.; Bradley, Elizabeth D.; Cato, Patrick A.; Gipson, Cassandra D.; Gray, Kevin M.
Highlights: NAC was evaluated for early and sustained abstinence and relapse prevention. NAC was safe and well-tolerated in adult daily smokers. NAC did not promote greater abstinence or delayed time to relapse. NAC is unlikely to be successful as a monotherapy for adult smokers. Abstract: Background: There is robust preclinical literature and preliminary clinical findings supporting the use of N -Acetylcysteine (NAC) to treat substance use disorders, including tobacco use disorder (TUD). However, randomized controlled trials have yielded mixed results and NAC's efficacy for TUD has not been established. The goals of this study were to assess the efficacy of NAC in promoting early and end-of-treatment abstinence and preventing relapse among adult smokers. Methods: This randomized, double-blinded clinical trial enrolled adult, daily smokers (N = 114; ages 23–64; 51 % female; 65 % White; 29 % Black/African American; 7% Hispanic/Latinx), who were randomized 1:1 to receive NAC (n = 59) or placebo (n = 55) (1200 mg b.i.d.) for eight weeks. Participants received brief cessation counseling and incentives for abstinence during the first three days of the quit attempt. Primary outcomes: (i) carbon monoxide (CO)-confirmed abstinence during the first three days of the quit attempt. Secondary outcomes: (ii) time to relapse; (iii) biologically confirmed abstinence at Week 8. Results: No differences were found between NAC and placebo groups on measures of early abstinence (3-day quit attempt; 11 % for NAC vs. 15 % for placebo; all p  > 0.11), time to relapse ( p  = 0.19), and end-of-treatment abstinence (7% for NAC vs. 11 % for placebo; all p  > 0.40]. Conclusions: Results indicate that NAC is a well-tolerated pharmacotherapy but is unlikely to be efficacious as a monotherapy for TUD in adults. Considered in the collective context of other research, NAC may potentially be more useful in a younger population, as a combination pharmacotherapy, or in the presence of more intensive psychosocial treatment.